Influence of Storage Conditions on Physico-Chemical Attributes of Strawberry–Aloe Vera Functional Gummies - Julie D Bandral; Jesreen Chauhan; Monika Sood; Neeraj Gupta; Skarma Choton; Anjali Langeh; Mehnaaza Bashir; Upma Dutta (Public Health, 2026)
The increasing demand for functional confectionery products has promoted the incorporation of bioactive ingredients to enhance nutritional and health benefits. In the present investigation, strawberry- aloe vera blended gummies were developed and evaluated for storage stability under ambient (25–30 °C) and refrigerated (4–8 °C) conditions over 90 days. Six formulations (T0–T6) with varying strawberry to aloe vera pulp ratios were analyzed at regular intervals for physico-chemical properties (moisture content, total soluble solids, titratable acidity, ash content, reducing sugars, and total sugars), microbial load, and sensory attributes. Moisture content increased significantly with higher aloe vera incorporation, with T6 (0:100::Strawberry:Aloe vera) exhibiting the highest values. During storage, total soluble solids and titratable acidity showed a gradual increase, whereas ash content declined. Although reducing and total sugars decreased with increasing aloe vera levels, both parameters increased progressively during storage, likely due to polysaccharide hydrolysis and moisture loss. The findings indicate that aloe vera enrichment enhances moisture retention but influences quality attributes during storage. Refrigerated storage proved more effective in maintaining the physico-chemical stability of the developed functional gummies.